Model vehicle routing problem untuk penentuan rute distribusi unit sepeda motor dengan metode saving matrix - Mohammad Cipto Sugiono (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2022)
PT X is a manufacturing company that produces motorcycle units. With the continuous increase of product demand from consumers, it makes PT X being one of the largest manufacturing companies in Indonesia. As long this determination of the distribution route is conducted by PT X only based on the experience and knowledge of the drivers. The distribution route should include the configuration of the appropriate distribution channels, in order for the delivery to be fast at a low cost. This problem is known as the Vehicle Routing Problem (VRP). To overcome the problem must conduct research in the hope to minimize the cost of distribution of motorcycle units to the dealers, that is by calculating fuel consumption, tolls chargers, bundles of units and loading and unloading. The problem Vehicle Routing Problem (VRP) is solved by using Saving Matrix method. The calculation result can minimize distribution costs of Rp3.323.500,-. While the actual cost of the company is Rp3.530.000,-. So it can be seen that there is a deease in the cost of Rp206.500/day. Model Vehicle Routing Problem (VRP) untuk penentuan rute distribusi unit sepeda motor dengan metode saving matrix